Intracytoplasmic sperm injection outcomes after anti-oxidant treatment in repeated implantation failure - Tangal, Semih; Çağlar, Gamze Sinem; Pabuçcu, Emre Göksan; Keskin, Müge; Haliloğlu, Ahmet Hakan (The European Research Journal, 2019)
Objectives: Aim of this study was to explore the effects of three months oral anti-oxidant treatment in normozoospermic men with high DNA fragmentation index (DFI) and recurrent intracytoplasmic sperm injection (ICSI) failures. Methods: This is a retrospective analyses of normozoospermic patients with high DFI levels (> 30%) with at least two unsuccessful ICSI attempts. Among the participants, the study group included men who had oral anti-oxidant treatment. The men who did not receive any treatment during the study period were taken as controls. The outcomes of new ICSI cycles were compared.Results: During the study period 24 men have used three months of oral anti-oxidant treatment before a new ICSI cycle whereas the remaining 46 had ICSI-only without any other intervention. Duration of stimulation, the number of metaphase II oocytes, fertilization rate and implantation rates were similar between two groups. Although not statistically significant, cases in anti-oxidant group have slightly better pregnancy rates compared to ICSI-only group (37.5% vs 19.6%, p > 0.05). Only one case in each group had abortion. Conclusions: This study reveals that there is no statistically significant difference in the ICSI outcomes of the patients with high DFI levels, following unsuccessful ICSI attempts after oral anti-oxidant treatment. The possible benefit derived from the anti-oxidant therapy needs to be clarified with clinical studies with greater study populations.